Strengthening Tobacco Control through Multi-Stakeholder Engagement: The Uttarakhand Tobacco-Free Coalition (UTFC) for Protecting Youth and Communities - Awadhesh Kumar; Mamta Thappa; Manish Kumar Singh; Prema Taneja; Sonu Goel (Global Health Cases, 2026)
Abstract Tobacco use remains a significant public health concern in Uttarakhand, with 26.5% of adults reported to use tobacco (Global Adult Tobacco Survey [GATS] 2016–17). Although national frameworks such as the Cigarettes and Other Tobacco Products Act (COTPA), 2003 and the National Tobacco Control Programme (NTCP) provide a clear policy direction, implementation at the state level continues to face practical challenges. These include difficult terrain, dispersed populations, and high population movement in pilgrimage areas. In response to these challenges, the Uttarakhand Tobacco-Free Coalition (UTFC) was established in July 2020 with support from Balajee Sewa Sansthan. The coalition was formed to bring together stakeholders from government departments, civil society, academia, and community groups on a common platform. Over time, regular meetings and interactions helped improve coordination and information sharing among members. The coalition has supported activities such as promotion of Tobacco-Free Educational Institutions (ToFEIs), installation of compliance signboards, and community awareness initiatives in coordination with district and state authorities. These efforts have contributed to improved visibility of tobacco control measures in different parts of the state. The experience suggests that structured coordination platforms can play an important role in strengthening implementation of tobacco control initiatives, particularly in settings with geographical and administrative challenges. Information © The Authors 2026